Igneous Rock Associations 30. Intratelluric Versus Subaerial Nucleation and Growth of Phenocrysts in Basaltic Lava Flows - Ross, Martin E. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2024)
Phenocrysts in porphyritic lava flows are generally considered to have grown under conditions of slow magma cooling within source reservoirs at depth. The matrix (i.e. groundmass) surrounding the phenocrysts is assumed to form under rapid cooling conditions subsequent to eruption of the residual liquids at the surface. Alternatively, it has been demonstrated experimentally that phenocrysts could grow subaerially in basaltic lavas cooled at constant, linear rates. It has been suggested this mechanism could explain the correlation of porphyritic textures with unusually thick canyon-filling flows of Columbia River Basalt. Field and petrographic data supports intratelluric nucleation and growth of plagioclase phenocrysts in three lavas of the Columbia River Basalt Group (CRBG).The distinction is important because the typical basaltic phenocryst paragenesis (plagioclase, followed by olivine, then augite), if produced under surface conditions, cannot be used to test fractional crystallization models in magma reservoirs of the Columbia River Basalt Group or any other lavas.Ideally, to test the hypotheses of subaerial vs. intratelluric (subsurface) growth of phenocrysts, both intrusive (i.e. dykes) and extrusive samples crystallized from the same liquid need to be examined to compare sizes and abundances of phenocrysts. If phenocryst growth occurs only subaerially, then a lava flow should contain more phenocrysts than its intrusive counterpart. In the case of nucleation and growth in both a dyke and its flow, the flow still would contain more phenocrysts due to grains formed in the dyke being added to those formed in the flow.Detailed modal and grain size data were collected for three dyke-flow pairs of CRBG by the author and provide an excellent opportunity to compare intrusive and extrusive textures. These findings along with XRF major and trace element data indicate that the phenocrysts in these lavas must have grown within the magma reservoir and not at the surface. A model is proposed that explains the variation of phenocryst distribution laterally within a lava as an interplay of variations of magma flow and the underlying paleo-topography.